Tingkat Kebahagian dengan Kualitas Hidup Pada Lansia yang Tinggal di Panti Werdha Jambangan Surabaya - Maria Manungkalit; Ni Putu Wulan Purnama Sari (Malahayati Nursing Journal, 2022)
ABSTRACT Happiness in old age is slightly lower than happiness in youth regardless of the setting in which the elderly live, in the community or in a nursing home. Happiness contains the aspects of positive emotions and life satisfaction that contribute to the quality of an individual's life. This study aimed to analyze the correlation between the level of happiness and the quality of life in Panti Werdha. This study used a cross-sectional design. The population was all elderly who live in a nursing home of Jambangan Surabaya. Total sampling was applied in this study. The sample size was 150 elderly. The independent variable was the level of happiness as measured by the OHQ instrument, while the dependent variable was the quality of life as measured by the OPQOL instrument. The statistical test used was the Spearman Rank correlation test (α0.05). Resulit 49.4% of respondents are elderly (75-90 years old), 52% of respondents are male, education level is 69.46%, 51.4% of respondents are widows/widowers and most of them have closeness to their children as much as 54, 35%. 38% of respondents have a history of working as private employees. Most of them have a moderate level of happiness (47.3%) but their quality of life was high (68.7%). There was a sufficient and significant correlation between the level of happiness and the quality of life in panti werdha (Rho = 0.456; p = 0.000). There is a strong and significant relationship between the level of happiness and the quality of life in the elderly living in panti werdha.  Keywords: Elderly, Happiness, Nursing Home, Quality Of Life ABSTRAK Kebahagiaan di masa tua memang sedikit lebih rendah dari kebahagiaan di masa muda terlepas dari di setting mana lansia itu tinggal, di komunitas atau di panti werdha. Di dalam kebahagiaan ada aspek emosi positif dan kepuasan hidup yang berkontribusi terhadap kualitas hidup individu. Penelitian ini bertujuan menganalisis hubungan tingkat kebahagiaan dengan kualitas hidup pada lansia yang tinggal di panti werdha. Penelitian ini menggunakan desain cross-sectional. Populasi adalah seluruh lansia yang tinggal di panti werdha Jambangan di Surabaya. Total sampling diterapkan dalam penelitian ini. Besar sampel 150 orang. Variabel independen adalah tingkat kebahagiaan yang diukur dengan instrumen OHQ, sedangkan variabel dependen adalah kualitas hidup yang diukur dengan instrumen OPQOL. Uji statistik yang digunakan adalah uji korelasi Rank Spearman (α0,05). Hasil 49,4% responden adalah lansia usia tua (75-90 tahun), 52% responden adalah laki-laki, tingkat pendidikan sebanyak 69,46%, 51,4% responden adalah janda/duda dan kebanyakan memiliki kedekatan dengan anaknya sebanyak 54,35%. 38% responden memiliki riwayat pekerjaan sebagai pegawai swasta. Sebagian besar memiliki tingkat kebahagiaan yang sedang (47,3%) namun kualitas hidupnya tinggi (68,7%). Ada hubungan yang cukup kuat dan signifikan antara tingkat kebahagiaan dengan kualitas hidup lansia yang tinggal di panti werdha (Rho=0,456; p=0,000). Terdapat hubungan yang kuat dan signifikan antara tingkat kebahagiaan dengan kualitas hidup pada lansia yang tinggal dipanti. Kata Kunci: Bahagia, Kualitas Hidup, Lansia, Panti Werdha